From amorphous to ordered: Structural transformation of Pd nanoclusters in 1-pentyne hydrogenation reactions - Richard Palmer (Journal of Catalysis, 2021)
Nanostructured palladium catalysts are used industrially for selective alkyne hydrogenation reactions. However, structural changes can lead to a loss of performance. In this study, we show the evolution of the atomic structure of monodispersed Pd nanoclusters undergoing a vapour-phase 1-pentyne hydrogenation reaction. A specific structural transformation, from amorphous to highly symmetrical structures, is observed at the atomic level with aberration-corrected scanning transmission electron microscopy (AC-STEM). This surprising behaviour which occurs concurrently with the alkyne hydrogenation reaction, is clearly size-dependent. The results provide new understanding of the long-term stability of commercial heterogeneous catalysts.